Targeted neural differentiation of murine mesenchymal stem cells by a protocol simulating the inflammatory site of neural injury - Chudickova, Milada; Bruza, Petr; Zajicova, Alena; Trosan, Peter; Svobodova, Lucie; Javorkova, Eliska; Kubinova, Sarka; Holan, Vladimir (Journal of tissue engineering and regenerative medicine, 2017)
Damaged neural tissue is regenerated by neural stem cells (NSCs), which represent a rare and difficult-to-culture cell population. Therefore, alternative sources of stem cells are being tested to replace a shortage of NSCs. Here we show that mouse adipose tissue-derived mesenchymal stem cells (MSCs) can be effectively differentiated into cells expressing neuronal cell markers. The differentiation protocol, simulating the inflammatory site of neural injury, involved brain tissue extract, fibroblast growth factor, epidermal growth factor, supernatant from activated splenocytes and electrical stimulation under physiological conditions. MSCs differentiated using this protocol displayed neuronal cell morphology and expressed genes for neuronal cell markers, such as neurofilament light (Nf-L), medium (Nf-M) and heavy (Nf-H) polypeptides, synaptophysin (SYP), neural cell adhesion molecule (NCAM), glutamic acid decarboxylase (GAD), neuron-specific nuclear protein (NeuN), βIII-tubulin (Tubb3) and microtubule-associated protein 2 (Mtap2), which are absent (Nf-L, Nf-H, SYP, GAD, NeuN and Mtap2) or only slightly expressed (NCAM, Tubb3 and Nf-M) in undifferentiated cells. The differentiation was further enhanced when the cells were cultured on nanofibre scaffolds. The neural differentiation of MSCs, which was detected at the level of gene expression, was confirmed by positive immunostaining for Nf-L protein. The results thus show that the simulation of conditions in an injured neural tissue and inflammatory environment, supplemented with electrical stimulation under physiological conditions and cultivation of cells on a three-dimensional (3D) nanofibre scaffold, form an effective protocol for the differentiation of MSCs into cells with neuronal markers. Copyright © 2015 John Wiley & Sons, Ltd.
Keywords: Antigens, Differentiation; adipose-derived mesenchymal stem cells; Mice, Inbred BALB C; Cell Differentiation; Inflammation; Neural Stem Cells; mouse; electrical stimulation; zánět; neural injury; Mice; Mesenchymal Stem Cells; nanofibre scaffold; diferenciační antigeny; mezenchymální kmenové buňky; Nerve Tissue; zvířata; myši inbrední BALB C; nervové kmenové buňky; neural differentiation; myši; buněčná diferenciace; nervová tkáň; Animals